Bahasa Inggris - Kevin Adhelacahya; Sukarmin Sukarmin; Sarwanto Sarwanto (Postgraduate, University of Mataram, 2023)
One of the goals of learning physics is to help students develop their critical thinking skills. Preliminary studies conducted at SMAN 1 Pacitan show that the learning process is still teacher-centered with the lecture method and providing practice questions. Such a learning process causes the development of student's critical thinking skills to be less well-stimulated. Using e-modules in physics learning is expected to be a new solution to stimulate students' critical thinking skills. This research aims to determine the impact of Problem-Based learning physics electronic module integrated with STEM on students' critical thinking skills. The research method uses a quasi-experimental technique with a one-group pretest-posttest design. Data analysis used the N-gain test to determine the increase in students' critical thinking skills and the t-test to determine the effect of problem-based learning electronic module integrated with STEM on students' critical thinking skills. The sample was selected using a purposive sampling strategy. The samples involved were 34 students of class XI MIPA Senior High School Pacitan. The test was conducted to collect data on students' critical thinking skills. Research data was collected using an essay test of critical thinking skills totaling twelve valid questions with a reliability coefficient 0.70. Before the N-gain test was carried out, the normality, homogeneity, and t-test were first carried out. In the normality test, the data is normally distributed. In the homogeneity test, the data is homogeneous. Based on the paired sample t-test, it shows that there is a significant difference between pretest and posttest critical thinking skills with a sig. (2-tailed) <0.05, which indicates that the problem-based learning electronic module integrated with STEM has a positive effect on students' critical thinking skills. By acquiring an N-Gain score of 0.76 in the high category, the PBL physics electronic module integrated with STEM on mechanical wave characteristics material can improve students' critical thinking skills.